Net Zero needs AI - five actions to realize its promise - Luers, Amy (Nature, 2025)
Without artificial-intelligence technologies, balancing human-caused greenhouse-gas emissions with carbon removals by 2050 is out of reach. Action in five areas is needed to keep this goal alive.